Short dual antiplatelet therapy duration after percutaneous coronary intervention in high bleeding risk patients: Systematic review and meta-analysis - Bainey, Kevin R.; Marquis-Gravel, Guillaume; MacDonald, Blair J.; Bewick, David; Yan, Andrew; Turgeon, Ricky D. (PloS one, 2023)
Dual antiplatelet therapy (DAPT) following percutaneous coronary intervention (PCI) reduces major adverse cardiovascular events (MACE) and stent thrombosis. However, DAPT duration is a concern in high bleeding risk (HBR) patients. We evaluated the effect of short DAPT (1-3 months) compared to standard DAPT (6-12 months) on bleeding and ischemic events in HBR PCI. We searched MEDLINE, Embase and CENTRAL up to August 18, 2022. Randomized controlled trials (RCTs) comparing short DAPT (1-3 months) versus standard DAPT in HBR PCI were included. We assessed risk of bias (RoB) using the Cochrane RoB2 tool, and certainty of evidence using GRADE criteria. Outcomes included MACE, all-cause death, stent thrombosis, major bleeding, and the composite of major or clinically-relevant non-major bleeding. We estimated risk ratios (RR) and 95% confidence intervals (CI) using a random-effects model. From 503 articles, we included five RCTs (n = 7,242) at overall low risk of bias with median follow-up of 12-months. Compared to standard DAPT, short DAPT did not increase MACE (RR 1.02, 95% CI 0.84-1.23), all-cause death (RR 0.92, 95% CI 0.71-1.20) or stent thrombosis (RR 1.47, 95% CI 0.73-2.93). Short DAPT reduced major bleeding (RR 0.34, 95% CI 0.13-0.90) and the composite of major or clinically-relevant non-major bleeding (RR 0.60, 95% CI 0.44-0.81), translating to 21 and 34 fewer events, respectively, per 1000 patients. In HBR PCI, DAPT for 1-3 months compared to 6-12 months reduced clinically-relevant bleeding events without jeopardizing ischemic risk. Short DAPT should be considered in HBR patients receiving PCI.